2003
DOI: 10.1053/rmed.2002.1454
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus parainfluenzae infection of respiratory mucosa

Abstract: The pathogenicity of Haemophilus parainfluenzae (Hpi) in the respiratory tract is unclear, in contrast to the accepted pathogenicity of its close relative non-typable H. influenzae. We have investigated the interaction of two Hpi isolates with the mucosa of adenoid and bronchial tissue organ cultures. The adherence of bacteria to the mucosa of organ cultures, the effect of broth culture filtrates on human nasal epithelium, and interleukin (IL)-8 production by A549 cell cultures was investigated. Hpi 4846 adher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…These observations suggest that colonisation by these PPMs is already able to induce an inflammatory response in the bronchial mucosa of such patients. This inflammatory response was seen to be species-specific because in our series, a similar effect was not found in COPD patients colonised by H. parainfluenzae, a PPM that occasionally causes COPD exacerbation and pneumonia [29][30][31], but has been shown to exhibit low mucosal adherence and a minimal potential to cause bronchial inflammation [32,33]. Our choice of H. influenzae load as a main study variable was justified by its close relationship to the inflammatory response of the bronchial mucosa.…”
Section: Copd and Smoking-related Disorders A Marin Et Almentioning
confidence: 72%
“…These observations suggest that colonisation by these PPMs is already able to induce an inflammatory response in the bronchial mucosa of such patients. This inflammatory response was seen to be species-specific because in our series, a similar effect was not found in COPD patients colonised by H. parainfluenzae, a PPM that occasionally causes COPD exacerbation and pneumonia [29][30][31], but has been shown to exhibit low mucosal adherence and a minimal potential to cause bronchial inflammation [32,33]. Our choice of H. influenzae load as a main study variable was justified by its close relationship to the inflammatory response of the bronchial mucosa.…”
Section: Copd and Smoking-related Disorders A Marin Et Almentioning
confidence: 72%
“…The inclusion of H. parainfluenzae in the group of PPMs may be controversial; however, this microorganism was included in the original definition of PPMs [18] and has been considered a respiratory pathogen, together with H. influenzae, in many studies dealing with bacterial colonisation in COPD [6,7,9,18,28]. In fact, MIDDLETON et al [42] demonstrated that H. parainfluenzae can be a pathogen in the lower respiratory tract when impaired airway defences delay bacterial clearance, as is the case in COPD. In any case, the frequency of isolation of this microorganism, both at inclusion and at 8 weeks, was similar in both treatment groups; therefore, excluding this isolation from the analysis would have not modified the results.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been undertaken to investigate the interaction of respiratory pathogens and their virulence factors with airway epithelium [2]. A number of bacterial pathogens that colonize the airways and cause respiratory tract infections, such as Streptococcus pneumoniae , Haemophilus influenzae , Staphylococcus aureus , Klebsiella pneumoniae and Pseudomonas aeruginosa , among many others, have been shown to produce factors which affect the ciliated epithelium [4,5,6,7,8,9,10,11,12,13]. These virulence factors appear to play a role in the pathogenesis of respiratory tract infections by disturbing ciliary structure or function, by stimulating mucus production and by damaging the structural integrity of the epithelium, thus enhancing colonization [5].…”
Section: Innate Immune Mechanismsmentioning
confidence: 99%